N-(4-Bromophenyl)-2,6-dimethyl-1,3-dioxan-4-amine - Zeenat Fatima; Gottimukkala Rambabu; Bandapalli Palakshi Reddy; Vijayaparthasarathi Vijayakumar; Devadasan Velmurugan (Acta Crystallographica Section E, 2013)
In the title compound, C12H16BrNO2, the dioxane ring adopts a chair conformation and its mean plane makes a dihedral angle of 60.63 (12)° with the 4-bromophenyl ring. In the crystal, molecules are linked by pairs of N—H...O hydrogen bonds, forming inversion dimers with an R22(8) ring motif. These dimers are consolidated by pairs of C—H...O hydrogen bonds with an R22(16) ring motif. Adjacent dimers are connected via C—H...O hydrogen bonds, forming infinite chains propagating along the c-axis direction.